2017
DOI: 10.1074/jbc.m117.814392
|View full text |Cite
|
Sign up to set email alerts
|

Cystine uptake through the cystine/glutamate antiporter xCT triggers glioblastoma cell death under glucose deprivation

Abstract: Oncogenic signaling in cancer cells alters glucose uptake and utilization to supply sufficient energy and biosynthetic intermediates for survival and sustained proliferation. Oncogenic signaling also prevents oxidative stress and cell death caused by increased production of reactive oxygen species. However, elevated glucose metabolism in cancer cells, especially in glioblastoma, results in the cells becoming sensitive to glucose deprivation ( in high glucose dependence), which rapidly induces cell death. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 43 publications
10
100
0
Order By: Relevance
“…5D). These findings corroborate recent reports that system xcactivity and expression is required for glucose deprivation-induced cell death 14,16,24 .…”
Section: L-cystine Drives Glucose Deprivation-induced Cell Deathsupporting
confidence: 92%
See 4 more Smart Citations
“…5D). These findings corroborate recent reports that system xcactivity and expression is required for glucose deprivation-induced cell death 14,16,24 .…”
Section: L-cystine Drives Glucose Deprivation-induced Cell Deathsupporting
confidence: 92%
“…Among the GBM cell lines, we found that A172 exhibited strong resistance, LN229 and U118MG exhibited medium sensitivity, and LN18, T98, and U87 exhibited high sensitivity to glucose deprivation ( Fig. 1A) 23,24 . For the sarcoma cell lines, HT161 and TC32 exhibited resistance and sensitivity, respectfully, to glucose deprivation (Supporting Fig.…”
Section: Metabolomics Identifies Accumulation Of L-cystine and L-cystmentioning
confidence: 96%
See 3 more Smart Citations